Determination of optimal conditions for activity of arginase in kidney of rabbit - Sengul, Beytullah; Erisir, Mine (Ankara Univ Press, 2018)
Optimum conditions for arginase in kidney tissue may differ from those for arginase of liver. Because optimum conditions for measuring arginase activity in rabbit kidney tissue were not determined, it was aimed to optimize arginase of rabbit kidney tissue and compare it with arginase of liver. In the present study, the kidneys of six New Zealand rabbits aged 1 year old were used. It was found to be preincubation temperature 53 degrees C, preincubation period is 15 minutes, incubation period is 10 minutes and optimum pH is 10.1 in NaHCO3-NaOH buffer for arginase in rabbit kidney tissue. Enzyme achieved its highest activity at 1 mM MnCl2 concentration. Km of arginase in rabbit kidney tissue for L-arginine was measured as 12.5 mM. It was determined that Mn+2 ions and preincubation at 53 degrees C were essential for the activation of the enzyme. As a result, optimal conditions for the kidney arginase were found to be different from those for the liver arginase. Our study indicates that arginases encoded by separate gene loci may have different optimal conditions.
Tavşan böbrek arginaz aktivitesi için optimal şartların belirlenmesi
Keywords: Arginase; kidney; optimization; rabbit